Forming Critical Thinking: The Role of Students’ Epistemic Beliefs and Styles of Learning in Russian Universities - Kseniya V. Tarasova; Daniil P. Talov; Irina A. Shcheglova; Taras V. Pashchenko; Anastasiia Yu. Beliaeva (Вопросы образования)
The role of epistemic beliefs in the formation of critical thinking with the direct use of an active approach in teaching in the context of higher education in Russia was studied within the framework of the presented research. In particular, a hypothesis of existence of a mediation effect of epistemic beliefs that enhances the effect of active school practices on the development of critical thinking was tested.